The Impact of Selected Macroeconomic Variables on Carbon Dioxide (Co2) Emission in Malaysia - Rambeli Ramli, Norimah; Abdul Jalil, Norasibah; Hashim, Emilda; Mahdinezhad, Maryam; Hashim, Asmawi; ., Belee; Mohd Bakri, Syazwani (International Journal of Engineering and Technology, 2018)
This study tries to investigate the relationship between gross domestic product, electricity product, net trade, electricity consumption and oil price on carbon dioxide (Co2) emission in Malaysia. Thus, it uses the Ordinary Least Square (OLS) method in structuring the model estimation. By utilizing yearly time series data from 1980 to 2017, this study focuses on economics and statistical criteria analyses. According to sign analysis, the results suggest that, gross domestic product, electricity product, net trade and energy consumption affect carbon dioxides (Co2) positively. In contrast, the oil price affects carbon dioxides (Co2) negatively. Furthermore, the results in statistical criteria conclude that the gross domestic product, electricity product and energy consumption are the dominant factors that influence carbon dioxides combustion in the long run in Malaysia.Â Â